Genetic parameters for reproductive trains in red tilapia (Oreochromis spp.) in the RIA2 of Vietnam : - Charles, Muhirwa Safari (Can Tho university, 2018)
This book introduce about produce families of 5th generation of red tilapia. Estimate genetic parameters for reproductive traits in red tilapia. Determine survival, fertility and hatching rate of red tilapia.